Teachers’ Challenging Experiences in Home Visitation During the New Normal Education: A Phenomenological Study - Buot, Jesscel Jane (Journal of Interdisciplinary Perspectives, 2024)
Home visits are intended to decrease the reading gap, improve parenting skills, foster parent-child contact and involvement, boost students' school preparedness and achievement, and advance literacy. The home visitation program was the only option for the teachers to validate their learners' academic performance during the Modular Distance Learning in the new normal education. This study explored the challenges that public elementary school teachers encountered in home visitation during the new normal education in Jimenez District, Division of Misamis Occidental. A phenomenological approach was utilized as a research design, with nine public elementary school teachers as participants in the study. They were selected through purposive sampling. Face-to-face interviews were conducted to gather the data from the participants. The responses were analyzed using Moustakas’ method of data analysis. Results generated the following themes: threats to one’s security and safety, inadequacies of interpersonal connections among teachers, parents, and learners, conflict of other school-related activities and teachers’ coping strategies. The study showed that teachers experienced different challenges in home visitation during the new normal education. When teachers leave the confines of the school campus to provide services in locations other than where they are employed, they expose themselves to a significant risk and face potential threats to their safety and security. When students and their parents are absent during a home visit, it can be difficult for teachers to administer assessments or validate student work. Teachers also find that overlapping school activities and home visitation make for an exhausting experience. However, the study showed that despite the challenges the teachers have encountered, they remain diligent and responsive to the needs of their learners. Teachers' coping strategies have assisted them in remaining optimistic and flexible in facing different challenges. The buddy system, total health, and time management among teachers are recommended in this study.